Wtórna nosowość antycypacyjna w Księgach o gospodarstwie Piotra Krescentyna z 1549 roku - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The article is a continuation of research concerning textual differences of the distribution of variant graphic and phonetic forms in the first Polish-language edition of Księgi o gospodarstwie by Piotr Krescentyn (Helena Unglerowa, 1549). The analysis comprised the markings of the secondary anticipatory nasality. The article proposes a graphic interpretation of this phenomenon. Such interpretation results from the recognition as common a phenomenon of nasalization of labial vowels before nasal consonants. Different distribution of the studied forms in the text proved significant – it revealed not only the segmentation of text already known from previous analyses (graphic and phonetic – boundaries 429/430 and 485/486), but also three new, previously unknown text boundaries running between columns 477/478, 501/502 and 531/532. The convergence of the separated boundaries with a division of text into typesets was confirmed three times. This attests to a strong dependence of the discussed phenomenon on the type-setting factor. A comparative analysis demonstrated that as far as marking the secondary nasality is concerned, Księgi bear witness of the condition unknown in other prints from this period, which is closer to some 16th-century manuscripts, especially the letters of Stanisław Koszucki.